Cultural intimacy : social poetics in the nation-state - Herzfeld, Michael 1947- (New York : Routledge, 1997)
In Cultural Intimacy, anthropologist Michael Herzfeld asks why officials treat certain features of national culture as disreputable, and why at the same time it is these features through which the nation-state often secures the loyalty of its citizens. To probe this "cultural intimacy" he develops an approach, which he calls "social poetics" that opens up the tensions between official models of national culture and the lived experience of ordinary citizens.
Cultural Intimacy draws on the author's own extensive fieldwork in Greece, as well as on a wide range of comparisons from the United States, Africa, Western Europe, and elsewhere. Herzfeld explores many topics - from sheep-thieves to flight attendants, from the banality of polite chit-chat to the divine vengeance invoked against perjury, and from the personal styles of coffeehouse and barroom to the politics of academia.
In all these arenas he finds revealing tensions between the formal idealization of collective self-recognition.
Includes bibliographical references and index.
Keywords: Nation-state.; Minorities; Group identity; Ethnicity